Prosperity and health ministry as a coping mechanism in the poverty and suffering context of Zimbabwe: A pastoral evaluation and response - Magezi, Vhumani; Manzanga, Peter (In die Skriflig, 2016)
Preaching on prosperity and health has significantly increased in Zimbabwe. Yet, poverty and suffering are also increasing, which is a contradiction. The preaching gives ‘hope’ of prosperity, wealth, health and success to its followers. The emerging question, however, is the following: What kind of hope is given? This article considers the Zimbabwean context of suffering and poverty, and the coping that arises from the Prosperity Gospel Movement. It is argued that this movement tends to grow rapidly where there are challenges such as poverty, unemployment and health problems. The article discusses prosperity-gospel trends in Zimbabwe and the history and tenets of the prosperity gospel. It also suggests reasons for the rise of the movement. The article concludes by providing an evaluation of the movement and offering a pastoral response.
free